Compressibility Behaviour Of Nibong Tebal Clay Treated With Cement-Caltite Stabilizer - Tiew, Keyue (Universiti Sains Malaysia, 2021)
Marine clay is a problematic soil that will cause severe settlement problem. Thus, the stabilization of marine clay is important. This research is aimed to determine the geotechnical index properties of Nibong Tebal clay, to determine the compressibility behaviour of Nibong Tebal clay treated with cement and Caltite stabilizer through one-dimensional consolidation test, and to evaluate the effectiveness of the cement and Caltite stabilizer by comparing the performance of untreated and treated Nibong Tebal clay. The Nibong Tebal clay was collected at USM Engineering Campus. Its geotechnical properties were studied, including moisture content, particle size distribution, Atterberg limit, and specific gravity. The compressibility of the undisturbed clay and the clay treated with cement and Caltite were determined through one-dimensional consolidation test. It was found that the clay is a high plasticity clay with plasticity index of 32%. It has high moisture content of 112.12% and is fully made up of silt and clay. The compression index (Cc), coefficient of volume compressibility (mv), and coefficient of consolidation (Cv) of the undisturbed clay is 1.27, 0.8m2/MN to 5m2/MN, and 0.43m2/year to 3.9m2/year, respectively. The high Cc, high mv and low Cv showed that it is very compressible. The compressibility of the clay reduced after treated with 10% cement. The improvement was more significant when it was treated with 10% cement+10% Caltite. The Cc and mv were reduced to 0.10 and 0.01m2/MN to 0.35m2/MN, respectively. The Cv was increased to 38.5m2/year to 472.1m2/year. Hence, the cement-Caltite treatment is more effective than the cement-treatment in reducing the compressibility of marine clay.